PRELIMINARY SCREENING RESISTANCE OF Musa GERMPLASMS FOR BANANA BUNCHY TOP DISEASE IN PURWODADI BOTANIC GARDEN, PASURUAN, EAST JAWA - Hapsari, Lia; Masrum, Ahmad (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2012)
Banana Bunchy Top Disease (BBTD) caused by Banana Bunchy Top Virus (BBTV) is one of the most serious banana diseases, constraint and devastate to the local and regional banana production. Some of banana cultivars were more readily infected by the virus, but considering no cultivars is resistant. The incidences of BBTD and the type and severity symptoms in natural conditions without any artificial inoculation were recorded. The observations results on 2009 showed that 12.14% of the total accessions indicated positively infected BBTD. The BBTD incidences were increased rapidly about twofolds per year, 28.57% in October 2011 and 54.29% in October 2011. The spread and development of BBTD is optimum at humid, high rainfall intensity and temperatures, high soil fertility and also low light intensity or shaded. The latest monitoring on February 2012 (62.14%) comprises of 64 accessions were positively infected and 39 accessions were symptomless. Those symptomless accessions were initially indicated as tolerant banana cultivars to BBTD e.g. Pisang Kepok (BBB), Pisang Sobo (BBB), Pisang Bandung (ABB), Pisang Nangka (AAB), Pisang Candi (AAB) and Â Pisang Raja Marto (AAB). These preliminary results are in agreement with several previous studies indicated that genotypes with one or two B genomes tend to be more tolerant to BBTD. However several cultivars which known tend to BBTD tolerant are indicated susceptible to Blood Disease. Some cultivars also showing complication symptoms both BBTD and Blood Disease.